9+3p-5t+3=

Simple and best practice solution for 9+3p-5t+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+3p-5t+3= equation:


Simplifying
9 + 3p + -5t + 3 = 0

Reorder the terms:
9 + 3 + 3p + -5t = 0

Combine like terms: 9 + 3 = 12
12 + 3p + -5t = 0

Solving
12 + 3p + -5t = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + 3p + -12 + -5t = 0 + -12

Reorder the terms:
12 + -12 + 3p + -5t = 0 + -12

Combine like terms: 12 + -12 = 0
0 + 3p + -5t = 0 + -12
3p + -5t = 0 + -12

Combine like terms: 0 + -12 = -12
3p + -5t = -12

Add '5t' to each side of the equation.
3p + -5t + 5t = -12 + 5t

Combine like terms: -5t + 5t = 0
3p + 0 = -12 + 5t
3p = -12 + 5t

Divide each side by '3'.
p = -4 + 1.666666667t

Simplifying
p = -4 + 1.666666667t

See similar equations:

| 31-7r=-6r-4(1-r) | | -5-2/7x=-1 | | -5-2/7x=25 | | 2(x+3)+5x=12 | | -90=5(2n-8) | | t/-6-8=7 | | 4+1/3y=-5 | | -3/2x-9=6 | | u/9=1 | | 5x/8=2x/3-1 | | 5x+13=9x-39 | | -7p+3p=8 | | 3lnx=2 | | 7z-8=3z+24 | | -2/5x-1=3 | | 777/6 | | -4(x+5)=3(x-11) | | 2x-0.3-2.6x=3.42 | | 2x*5=11 | | v+5=8 | | 8=-5/6z-12 | | 2-3(3x-4)+5=52 | | -3(x+8)-2(4x-3)=-7 | | -3=5v-5 | | Xlnx=6lnx | | x+3.5=9 | | (4f+5)-(-5f-40)=180 | | -94-x=-12x+49 | | 13x^2-16x=4 | | 4(k+5)=2(9t-2) | | 4(v-8)=-2v-26 | | 8x=-8x-7x |

Equations solver categories